Determination and stability of divicine and isouramil produced by enzymatic hydrolysis of vicine and convicine of faba bean. (1st December 2016) - Pulkkinen, Marjo; Zhou, Xiao; Lampi, Anna-Maija; Piironen, Vieno
Highlights: Vicine, convicine and their toxic aglycones can be analysed by the same HPLC method. Degradation of toxic aglycones was shown in conditions relevant to food processing. Sodium ascorbate slowed degradation of divicine. Abstract: The aglycones of vicine and convicine, divicine and isouramil, are the causative agents of favism and, therefore, should be analysed along with vicine and convicine in research seeking to eliminate them. This study investigated the stability of the aglycones produced by hydrolysis with β-glucosidase. Reversed-phase, high-performance liquid chromatography (HPLC) with UV detection was shown to be able to observe both aglycone formation and further reactions in isolated fractions and extract made from faba bean and in faba bean suspension. Divicine and isouramil were unstable and degraded almost completely in extract in 60 min and completely in fractions in 120 min at a pH of 5 at 37 °C. Adding sodium ascorbate delayed degradation of divicine. Divicine was more stable at 20 °C than at 37 °C. Being able to show formation and degradation of the aglycones, the proposed method allows monitoring of the vicine and convicine detoxification process.